1994
DOI: 10.1523/jneurosci.14-03-01746.1994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of nitric oxide synthase expression with changing patterns of axonal projections in the developing visual system

Abstract: A precise pattern of connections between the retina and central visual nuclei in the brain is established during development. Activity-dependent presynaptic mechanisms and NMDA receptor-mediated postsynaptic mechanisms are thought to play important roles in this developmental process. A model proposed for production of the newly described neurotransmitter, nitric oxide, involves presynaptic activity and activation of postsynaptic NMDA receptors. If present in the developing visual system, nitric oxide could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(85 citation statements)
references
References 33 publications
(33 reference statements)
4
76
3
2
Order By: Relevance
“…In the abalone Haliotis rufescens, cerebral serotonergic neurons that innervate the velum are most likely lost by cell death (Barlow and Truman, 1992). In mammals, changes in NOS activity correlate with synaptogenesis and cell death (Bredt and Snyder, 1994;Williams et al, 1994;Ogilvie et al, 1995), two processes common to developing nervous systems. Edelman and Gally (1992) have suggested that NO could function to coordinate the development of groups of interactive neurons, but further experiments would be necessary to document this phenomenon in developing Ilyanassa.…”
Section: Discussionmentioning
confidence: 99%
“…In the abalone Haliotis rufescens, cerebral serotonergic neurons that innervate the velum are most likely lost by cell death (Barlow and Truman, 1992). In mammals, changes in NOS activity correlate with synaptogenesis and cell death (Bredt and Snyder, 1994;Williams et al, 1994;Ogilvie et al, 1995), two processes common to developing nervous systems. Edelman and Gally (1992) have suggested that NO could function to coordinate the development of groups of interactive neurons, but further experiments would be necessary to document this phenomenon in developing Ilyanassa.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is no evidence to support the hypothesis that the cells adjacent to the AMNs undergo cell death. Therefore, an equally valid alternative is that this group of diaphorase-positive cells, like SMNs, DRG, and a number of other neurons (Bruning, 1993;Cramer et al, 1993;Gonzalez-Hernandez et al, 1993Kalb and Agostini, 1993;Ward et al, 1994;Williams et al, 1994), may express diaphorase activity only transiently during development.…”
Section: Cells That Transiently Express Diaphorase Activity During Dementioning
confidence: 99%
“…1°2. 122 It should be noted that the distribution of diaphorase-positive neurons in several neural structures had been described, albeit not quantitatively, prior to its association with NOS had been established. 2° '27"34"6°'61,l°9 '117'l18 1987).…”
mentioning
confidence: 99%